Nothing lasts forever - Sheldon, Sidney (Beverly Hills, CA : London: Dove Audio, HarperColling Publisher, 1994)
Nothing lasts forever races from the operating room to the court room amidst the ambitions and fears of healers and killers, lovers and betrayers.
Abridged.
Sidney Sheldon.
Keywords: Women physicians -- United States -- Fiction